The poly(A) tail length of casein mRNA in the lactating mammary gland changes depending upon the accumulation and removal of milk. - Kuraishi, T (2000)
The length of casein mRNA from the lactating mouse mammary gland, as assessed on Northern blots, is shorter after weaning, but is elongated following the removal of milk. In order to investigate this phenomenon, the molecular structures of beta- and gamma-casein mRNAs were analysed. The coding and non-coding regions of the two forms were the same length, but the long form of casein mRNA had a longer poly(A) tail than the short form (P<0.05). In order to examine the stability of casein mRNA under identical conditions, casein mRNAs with the long and short poly(A) tails were incubated in the rabbit reticulocyte lysate (RRL) cell-free translation system. Casein mRNA with the long poly(A) tail had a longer half-life than that with the short tail (P<0.05). The beta- and gamma-casein mRNAs were first degraded into 0.92 and 0.81 kb fragments respectively. With undegraded mRNA, the poly(A) tail shortening by exoribonuclease was not observed until the end of the incubation. Northern blot analysis showed that casein mRNA with the long poly(A) tail was protected efficiently from endoribonucleases. We conclude that the length of the poly(A) tail of casein mRNA in the lactating mammary gland changes depending upon the accumulation and removal of the gland's milk, and we show that the longer poly(A) tail potentially protects the mRNA from degradation by endoribonucleases.